August Snow [large type] - Jones, Stephen Mack (Thorndike Press, a part of Gale, Cengage Learning, 2017)
From the wealthy suburbs to the remains of Detroit's bankrupt factory districts, August Snow is a fast-paced tale of murder, greed, sex, economic cyber-terrorism, race and urban decay. Tough, smart, and struggling to stay alive, August Snow is the embodiment of Detroit. The son of an African-American father and a Mexican-American mother, August grew up in the city's Mexicantown and joined the police force only to be drummed out by a conspiracy of corrupt cops and politicians. But August fought back; he took on the city and got himself a $12 million wrongful dismissal settlement that left him low on friends. He has just returned to the house he grew up in after a year away, and quickly learns he has many scores to settle. It's not long before he's summoned to the palatial Grosse Pointe Estates home of business magnate Eleanore Paget. Powerful and manipulative, Paget wants August to investigate the increasingly unusual happenings at her private wealth management bank. But detective work is no longer August's beat, and he declines. A day later, Paget is dead of an apparent suicide--which August isn't buying for a minute. What begins as an inquiry into Eleanore Paget's death soon drags August into a rat's nest of Detroit's most dangerous criminals, from corporate embezzlers to tattooed mercenaries.